Dataset on the effect of perceived educational support on entrepreneurial intention among Vietnamese students - Nguyen, Hieu Thanh (Data Brief, 2021)
This article illustrates the dataset that explores the effects of perceived educational supports on entrepreneurial self-efficacy, attitude towards entrepreneurship, subjective norms, perceived behavioral control and entrepreneurial intention. The scales from previous studies were adopted to develop the questionnaires using the five-Likert scale. 2218 fulfilled responses were included in the sample, which recruited from fourteen universities in Vietnam with the similar index. Also, a quantitative method was utilized to examine the dataset. Cronbach's alpha was used to test the reliability of each construct, then explore factory analysis was employed to estimate factor loadings of each observed variables and the validity and discrimination of variables was tested through confirmatory factor analysis. Then, the structural equation modelling was used to estimate the effects of perceived educational support on entrepreneurial intention as well as the other paths.